2005
DOI: 10.1109/tpwrs.2005.858029
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of Higher Order Terms for Small-Signal (Modal) Analysis: Committee Report—Task Force on Assessing the Need to Include Higher Order Terms for Small-Signal (Modal) Analysis

Abstract: Abstract-This paper summarizes the work done by the Task Force on Assessing the Need to Include Higher Order Terms for Small-Signal (Modal) Analysis. This Task Force was created by the Power System Dynamic Performance Committee to investigate the need to include higher order terms for small signal (modal) analysis. The focus of the work reported here is on establishing and documenting the practical significance of these terms in stability analysis using the method of Normal Forms. Special emphasis was placed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(96 citation statements)
references
References 28 publications
2
94
0
Order By: Relevance
“…Thus, the results from the modal analysis are only valid in proximity of the linearization point and should be perceived as a snapshot of the dynamic system behavior. The method of normal forms offer a framework for extending the modal analysis to include higher order terms and thereby capture dynamics not captured by a linear model [27], [28]. This method is especially important for stressed, highly nonlinear power systems which are not accurately described by the linear approximation in (1).…”
Section: A Eigenvalue Analysismentioning
confidence: 99%
“…Thus, the results from the modal analysis are only valid in proximity of the linearization point and should be perceived as a snapshot of the dynamic system behavior. The method of normal forms offer a framework for extending the modal analysis to include higher order terms and thereby capture dynamics not captured by a linear model [27], [28]. This method is especially important for stressed, highly nonlinear power systems which are not accurately described by the linear approximation in (1).…”
Section: A Eigenvalue Analysismentioning
confidence: 99%
“…However, the bifurcation theory which is still at the exploratory stage cannot be applied to the large-scale system. Quadratic term is used to study the interactive effect between deferent modes based on the theory of normal forms method [15,16] and the modal series method [17,18]. However, these methods are complicated, and they can only reflect the nonlinear characteristics of equilibrium point and points nearby, but cannot count greater-range nonlinear factors in.…”
Section: Effects Of Nonlinearity On Low Frequency Oscillationmentioning
confidence: 99%
“…It is shown that the eigenvalue space of Carleman linear model is formed by the eigenvalues from the linear space of the matrix 1 1 A , 2 1 A and the matrix 1 A N , which contain eigenvalues associated with the higher-order modal interaction.…”
Section: Modal Analysis Of Carleman Linearizationmentioning
confidence: 99%
“…Reconsider (8) and (12), it is found that the higher-order terms 1 A k have been replaced by 1 A k in the process of obtaining eigenvalues and solution. In other words, the 2 nd order combined eigenvalues belong to 2 1 A but do not belong to 1 2 A .…”
Section: Solving the Truncated Carleman Linearized Model By Poincaré mentioning
confidence: 99%
See 1 more Smart Citation